1990
DOI: 10.1177/00220345900690111301
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Approximal Tooth Contact Tightness with Postural Change

Abstract: In order to investigate the role played by posture in determining posterior dental contact tightness, we measured contact tightness of maxillary and mandibular posterior teeth in ten adult subjects, while each was initially seated upright, after each had assumed a supine posture for two h, and finally after each had returned to an upright posture for two h. The technique used for measurement of contact tightness was based on frictional force concepts and consisted of the recording of the force required to with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
1
25
0
4
Order By: Relevance
“…This might have some effect on the measurement of the proximal contact strength, but is inevitable as adjustment of the adjacent restoration is mandatory for 'good clinical practice'. In a study of Southard et al, 9 it has been shown that when a patient was positioned horizontally, the proximal contact strength decreased over time. Therefore, in the present study the test readings were corrected based on the difference between baseline and final recording on the untreated control side of each patient in order to exclude possible influences.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This might have some effect on the measurement of the proximal contact strength, but is inevitable as adjustment of the adjacent restoration is mandatory for 'good clinical practice'. In a study of Southard et al, 9 it has been shown that when a patient was positioned horizontally, the proximal contact strength decreased over time. Therefore, in the present study the test readings were corrected based on the difference between baseline and final recording on the untreated control side of each patient in order to exclude possible influences.…”
Section: Discussionmentioning
confidence: 97%
“…8,9 Therefore, the contact strength at the experimental side after treatment (T 1 ) was corrected with the mean difference (T 1 KT 0 ) in proximal contact strength at the control side. Data were statistically analyzed using SPSS 12.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] In vivo, the contact strength is influenced by several factors, including tooth type, location of the tooth, time of day, 3 postural change, 28 periodontal condition of the tooth 29 and showing a high individual variability. The foregoing parameters are difficult to simulate in laboratory conditions and, at the same time, their impact cannot be easily assessed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…29 We input the coefficient of friction, 0.2, into the program to simulate the contact between the rest and tooth, and used 0.5 to simulate the proximal contact between the adjacent teeth. 30 As the boundary condition, all nodes on the crown surface of the first premolar were fixed. The zero displacement was also prescribed for all nodes on the outer surface of the PL surrounding the root of the second premolar.…”
Section: Methodsmentioning
confidence: 99%